Faktor Yang Mempengaruhi Kinerja Pegawai Dilihat Dari Disiplin dan Motivasi Kerja (Studi Pada Kantor Dinas Sosial Kabupaten Solok) - Sriyanti, Esi; Roza, Seflidiana; Ariyani, Desi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Well-performing personnel are a major source of motivation for social care agencies. Employee motivation and discipline are good indicators of this. Finding out how work motivation and discipline affected employees' performance at the Solok Regency Social Service Office was the aim of this study. This research falls under the category of quantitative research. The primary data that was used was gathered by having respondents fill out questionnaires. The study's population comprised all 39 employees who worked at the Solok Regency Social Service Office. Total sampling was the method employed for sampling in this investigation. 39 persons were the total number of samples that were to be used. Multiple linear regression analysis, determination coefficient testing, hypothesis testing, and research instrument testing were all used in the data analysis technique. The study's findings showed that work motivation affected employee performance, work discipline had no effect on employee performance, and work motivation and discipline had an impact on employee performance at the same time.